Ocean speaks : how Marie Tharp revealed the ocean's biggest secret - Keating, Jess (Tundra Books, 2020)
From a young age, Marie Tharp loved watching the world. She loved solving problems. And she loved pushing the limits of what girls and women were expected to do and be. In the mid-twentieth century, women were not welcome in the sciences, but Marie was tenacious. She got a job in a laboratory at Cambridge University, New York. She mapped the ocean floor point after point and slowly revealed a deep rift valley in the ocean floor. The mid-ocean ridge that Marie discovered is the single largest geographic feature on the planet, and she mapped it all from her small, cramped office.